Peran Komunitas dalam Membentuk Resiliensi Penyandang Disabilitas: Studi Fenomenologis Komunitas Sahabat mata - Fatiha Muthiazahra; Novia Rizky Kamilulfalah; Tribuana Tunggal Dewi; Siti Hikmah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
People with disabilities, especially the blind, still face various structural and cultural barriers that impact their psychological well-being and ability to participate in social life. Resilience is an important aspect that enables blind individuals to recover from pressure, stigma, and environmental limitations. This study aims to understand the role of the Sahabat Mata Community in shaping the resilience of its members. This study is a qualitative study using a phenomenological approach involving three subjects, namely members and administrators of the Sahabat Mata Community (KSM). Data collection methods were carried out through semi-structured interviews, participant observation, and document studies. The results of the study indicate that the Sahabat Mata Community (KSM) has contributed to the resilience of its members based on seven aspects of resilience according to Reivich & Shatte including emotional regulation, impulse control, optimism, problem-analyzing ability, self-efficacy, empathy, and achievement. The formation of resilience is strengthened through social processes, emotional support and opportunities to achieve self-potential formed in the Sahabat Mata Community. The findings of this study reveal that the Sahabat Mata Community as an inclusive community plays a role as a safe space for the formation of resilience of people with disabilities.